Microfinanzas para mujeres empresarias y desarrollo local. El caso del programa ConMujer en Michoacán - Morillón Noriega, Karen (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The microfinances institutions, who are responsible to assign money resources let to free tendencies, market the uncertain future of poor women, who receive microfinances. In the past, it is observed that to include that women to occupancy market is not enough to change the permanent subordination of women, and neither it is enough to change the gender’s relationship that has been presented in the society. It is required to understand the empowerment gain like a heterogeneous and multidimensional process to visualize the systemic and structural problem about authority relationships in development. For this reason, it is important the entailment of different local performers to strengthening in business field and empowerment gain of businesswoman in different dimensions of local development: Political, institutional, economic, social, cultural, spiritual and environmental. So, the economic resource administration does not have the responsibility of authority gain of women, this responsibility can be shared, if the microfinances institutions produce opportunities for autonomy of businesswoman in the different dimensions of development. In this way, the microfinances have the potential to be tools that enable the autonomy of businesswoman, and those ones become factors for local development.

Las instituciones de micro financiamiento correspondientes a la asignación de un recurso monetario, dejan a las libres fuerzas del mercado el futuro incierto de las mujeres pobres que reciben microcréditos. La experiencia del pasado enseña que, incorporarlas al mercado laboral no cambia la latente subordinación de las mujeres ni las relaciones de género que permean a la sociedad. Se requiere comprender el empoderamiento como un proceso heterogéneo y multidimensional para visualizar el problema sistémico-estructural de las relaciones de poder en el desarrollo. De aquí la importancia de la vinculación de las diferentes actoras y actores locales para el fortalecimiento empresarial y el empoderamiento las mujeres empresarias en las distintas dimensiones del desarrollo local: político, institucional, económico, social, cultural, espiritual y ambiental. Así, la responsabilidad del empoderamiento de las mujeres no recae en la administración de un recurso económico, se vuelve compartida cuando las instituciones de micro financiamiento generan condiciones para la agencia y la autonomía de las mujeres empresarias en las distintas dimensiones del desarrollo. De esta manera, las micro finanzas se potencializan como herramientas que posibilitan la autonomía y agencia de las mujeres empresarias, y contribuyen en los procesos de desarrollo local.
Facultad de Economía Vasco de Quiroga. Maestría en Ciencias en Desarrollo Local
Keywords: info:eu-repo/classification/cti/5; FEVAQ-M-2014-2046; Instituciones; Empoderamiento; Desarrollo local; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4986